Extrasynaptic volume transmission and diffusion parameters of the extracellular space - Syková, E (Neuroscience, 2004)
Extrasynaptic communication between neurons or neurons and glia is mediated by the diffusion of neuroactive substances in the volume of the extracellular space (ECS). The size and irregular geometry of the diffusion channels in the ECS substantially differ not only around individual cells but also in different CNS regions and thus affect and direct the movement of various neuroactive substances in the ECS. Diffusion in the CNS is therefore not only inhomogeneous, but often also anisotropic. The diffusion parameters in adult mammals (including humans), ECS volume fraction alpha (alpha=ECS volume/total tissue volume) and tortuosity lambda (lambda(2)=free/apparent diffusion coefficient), are typically 0.20-0.25 and 1.5-1.6, respectively, and as such hinder the diffusion of neuroactive substances and water. These diffusion parameters modulate neuronal signaling, neuron-glia communication and extrasynaptic "volume" transmission. A significant decrease in ECS volume fraction and an increase in diffusion barriers (tortuosity) occur during neuronal activity and pathological states. The changes are often related to cell swelling, cell loss, astrogliosis, the rearrangement of neuronal and astrocytic processes and changes in the extracellular matrix. They are also altered during physiological states such as development, lactation and aging. Plastic changes in ECS volume, tortuosity and anisotropy significantly affect neuron-glia communication, the spatial relation of glial processes toward synapses, glutamate or GABA "spillover" and synaptic crosstalk. The various changes in tissue diffusivity occurring during many pathological states are important for diagnosis, drug delivery and treatment.
Keywords: mezibuněčná komunikace; signální transdukce; Signal Transduction; Water-Electrolyte Balance; Presynaptic Terminals; Humans; neurotransmiterové látky; centrální nervový systém; Extracellular Fluid; Neurotransmitter Agents; presynaptická zakončení; lidé; zvířata; Cell Communication; Synaptic Transmission; difuze; nervový přenos; Diffusion; vodní a elektrolytová rovnováha; extracelulární tekutina; Central Nervous System; Animals